Comparative analysis of key flavor compounds in various baijiu types using E- nose, HS-SPME-GC–MS/MS, and HS-GC-IMS technologies - Yongji Huang; Ling Wang; Yulang Li; Yunxin Chen; Guangjing Chen; Luyu Jia; Yonghui Ge (Food Chemistry: X, 2025)
To investigate the differences in key volatile components among different types of baijiu, this study utilized E- nose, HS-SPME-GC–MS/MS, and HS-GC-IMS to identify key volatile compounds in four baijiu samples: Sauce-flavor (SAF), Thick Sauce-flavor (TSF), Strong-flavor (STF), and Light-flavor (LF). baijiu total of 35, 29, 8, and 12 key volatile components were identified in SAF, TSF, STF, and LF samples, respectively. Based on these findings, the study explored the differences and correlations in aroma profiles among different baijiu aroma types. The results provide valuable insights for baijiu flavor differentiation and product optimization while also offering a theoretical foundation for in-depth research on baijiu aroma and the development of new products.